Productive efficiency and trade opportunities for Kazakhstan dairy farms - Han, Sang Woo; Lim, Song Soo; Balkibayeva, Aida (Economia agro-alimentare/Food Economy - Open Access, 2021)
This study analyses the productive efficiency of dairy farms in Kazakhstan and suggests export implications by the expansion of trade networks and the participation of global value chains. As the world’s largest landlocked country and ninth largest area in the world, Kazakhstan has often been considered to have vast potential to produce and export dairy products. The greater openness of markets and improved geostrategic circumstances with the latest rail link between China and Europe are expected to strengthen Kazakhstan’s trade opportunities with the rest of the world. Despite these positive prospects, few empirical studies have examined the export potential of the country’s dairy products. To bridge this gap, this study surveys 23 dairy farms across nine oblasts in Kazakhstan and performs a data envelopment analysis with milk production as the output variable and feed, labour, and capital as the input variables. The estimation results indicate that Kazakh dairy farms could reduce input use by up to 70% under the most efficient system. A dichotomy of productive efficiency among large and capital-intensive versus small-scale family farms suggests that the country should promote inclusiveness through sharing knowledge and best practices within the industry.